The strain of representation how parties represent diverse voters in western and eastern Europe - Rohrschneider, Robert; Whitefield, Stephen (Oxford : Oxford University Press, 2012)
'The Strain of Representation' examines the quality of democratic representation in Europe, focusing on the way that political parties channel the preferences of different groups of citizens into government policies.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Representative government and representation -- Europe; Political parties -- Europe -- Platforms